2012
DOI: 10.7314/apjcp.2012.13.11.5671
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-arrestin 1 in Gastric Cardiac Adenocarcinoma and its Relation with Progression

Abstract: Objective: Arrestins act as mediators of G protein-coupled receptor (GPCR) desensitization and trafficking, also actin as a scaffold for many intracellular signaling network. The role that β-arrestin 1 plays in gastric cardiac adenocarcinoma (GCA) and its clinicopathologic significance are untouched. Methods: Fifty patients with gastric cardiac adenocarcinoma were retrospectively enrolled and β-arrestin 1 was detected using immunohistochemistry in tissue samples. Results: Nuclear expression of β-arrestin 1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…[ 12 , 13 , 25 ] In past studies, high expression of β-arrestin1 was associated with unfavorable clinicopathological parameters, such as histological grade, tumor size, lymph node metastases, distant metastases, and so on. [ 26 , 27 ] In the present study, we found that neither β-arrestin1(C) nor β-arrestin1(N) had a correlation with age, sex, smoking status, drinking status, grade of differentiation, tumor location, T stage, lymph node involvement, pathological stage, or the type of surgical procedure.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…[ 12 , 13 , 25 ] In past studies, high expression of β-arrestin1 was associated with unfavorable clinicopathological parameters, such as histological grade, tumor size, lymph node metastases, distant metastases, and so on. [ 26 , 27 ] In the present study, we found that neither β-arrestin1(C) nor β-arrestin1(N) had a correlation with age, sex, smoking status, drinking status, grade of differentiation, tumor location, T stage, lymph node involvement, pathological stage, or the type of surgical procedure.…”
Section: Discussioncontrasting
confidence: 70%
“…[ 26 ] In addition, Wang et al documented that β-arrestin1 had no relationship with the prognosis of gastric cardia adenocarcinoma. [ 27 ] Santulli proposed that, in the adrenal medulla, β-arrestin1 and G-protein-coupled receptor kinases 2 (GRK2) finely regulated the secretion of catecholamines. But in the heart, β-arrestin1 and GRK2 inhibited β-adrenergic receptor (βAR)-mediated inotropic effects, which was detrimental to cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…24 Wang et al studied that β-arrestin 1 was strikingly correlated with lymph nodal metastasis and pathological lymph nodal staging. 25 As expected, the results revealed that β-arrestin1 could promote the migration and invasion of ESCC cells. What's more, β-arrestin1 accelerated the process of EMT in ESCC cells and subcutaneous xenotransplanted tumors, while β-arrestin1 interference could inhibit migration, invasion and process of EMT in ESCC.…”
Section: Discussionsupporting
confidence: 74%
“…Their functional disparities might be explained by the minor differences in their sequences [16]. Unfortunately, our results of β-arrestin2 expression status in the current patients cohort were quite limited because of unknown experimental abnormalities; at last, we only collected efficient immunohistochemistry results in 36 adenocarcinoma specimens: 23 showed deletion of expression, 13 showed expression, including 2 high expression (staining score≥8), but COX survival analysis showed no prognostic significance of β-arrestin2 (univariate: binary variable, P=0.297; categorical variable, P=0.353).…”
Section: Discussionmentioning
confidence: 98%
“…However, the expression of β-arrestins in primary tumors has not been widely investigated, and their clinical significance is also not well revealed yet. To the best of our knowledge, only a few studies analyzed β-arrestin1 expression in primary tumors [14][15][16]. Thus, we conducted this research to explore the expression status of β-arrestin1 in non-small cell lung cancer (NSCLC) to further discuss its clinicopathologic significance.…”
Section: Introductionmentioning
confidence: 96%